To Be or Not To Be a Genius: The Argument for Acquired Knowledge and Life Experience - Whittemore, Hank (Journal of Scientific Exploration, 2023)
The personal attitudes and experiences of the greatest authors are usually reflected in their works, a phenomenon that gives literary biography its rich potential for new revelations and insights. Within this premise, the Shakespearean poems and plays appear to reflect the viewpoint and education of a high-ranking Elizabethan nobleman of vast experience and deep learning. In fact, many aspects of the life of Edward de Vere, 17th Earl of Oxford, appear to be closely mirrored by the title character of Hamlet, Prince of Denmark. Both the Earl and the Prince are each on intimate terms with a female monarch; each is involved with the daughter of the Queen’s chief minister; each brings actors to perform at the royal court; and while the author of Hamlet demonstrably referred to classics of the Italian Renaissance-- The Courtier and Cardanus’ Comforte -- Oxford himself sponsored publications of both these works in England. The specific focus of this essay is on aspects of such “special knowledge” within the Shakespearean works, special knowledge that has no specific connection to the life of the man from Stratford but which was deeply imbued in the life of Edward de Vere. Cited here will be details of the author’s connections to France and the French language; to the unique culture and geography of Italy; to the literature and drama of ancient Greece; to legal terminology and intricacies of the law; his proximity to persons and places of state power; to his military expertise; his medical knowledge; his intimacy with the sea and seamanship; to astronomy; to music; horses and horsemanship; heraldry; and to plants gardens and gardening. Such experiences and knowledge was possessed by the Earl of Oxford, and it is contrasted here with the paucity of similar experience and learning in the life of Will Shakspere of Stratford. The evidence clearly suggests that it was Edward de Vere using the pseudonym William Shakespeare rather than Will Shakspere who actually was behind the Bard’s work.